University Students’ Perceptions, Knowledge, and Behavioral Responses Toward Cyberbullying in Higher Education - Maikel Basten (PT. Global Research Collaboration, 2025)
Background/Context: Cyberbullying has become a serious threat to student mental health in the digital era, alongside rising internet penetration. While psychological impacts such as stress, anxiety, and depression are well documented, its effects on academic performance, morality, and empathy remain less understood.Objective/Purpose: This study aims to examine the impact of cyberbullying on university students, focusing on knowledge, attitudes, behavioral responses, and factors shaping their perceptions and experiences.Method: A quantitative survey was conducted with 185 students using a validated questionnaire. The instrument measured knowledge, attitudes toward digital media, and experiences and behaviors in responding to cyberbullying. Data were analyzed with descriptive statistics.Results: Most students showed good knowledge and awareness of cyberbullying and ethical digital behavior. However, few had direct experience, indicating a gap between theoretical understanding and practical exposure. No direct link with academic performance was found, though psychological effects may influence focus and motivation.Conclusion: Students demonstrate strong theoretical awareness but limited real-life experience. The study highlights the need for further research on moral, empathetic, and cross-platform implications of cyberbullying